Writer and Process: A Success Story Waiting to Happen - Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
It is time to face the facts. Every day we are asked to write more and more in English. Our academic existence is dependent on whether we can publish in English or perish (Mauranen, Pérez-Llantada, & Swales, 2010).  English has become the lingua franca of science and knowledge, but what happens when the structures and rules of standard Academic Writing seem to be against us?  Well, writers learn to adapt. We use translators, copy model structures, look for outside help, hire proofreaders, and talk to teachers. Despite our efforts, only a few writers become successful. What if we could find a solution within our own context? What if these successful writers had a secret to share with the rest of us? After all, every individual has been through a “writing process”, a series of events that have shaped the writer. By looking at the events that made successful writers who they are, we could understand how to better improve teaching practices in writing, develop efficient writing strategies, and promote individual writing styles all within our own context.